Approaching information-seeking habits and their contextual features - Reijo Savolainen (Information Research: An International Electronic Journal)
Introduction. In information seeking, habits manifest themselves in the ways in which people repeatedly and regularly prefer and access certain sources of information. The present study reviews how researchers in diverse field have approached such habits and characterised their contextual features.